Retrospective study of Bovine herpesvirus 5 meningoencephalitis in cattle from São Paulo State, Brazil - Cagnini, D. Q. [UNESP]; Andrade, D. G.A. [UNESP]; Cunha, P. H.J.; Oliveira-Filho, J. P. [UNESP]; Amorim, R. L. [UNESP]; Alfieri, A. A.; Borges, A. S. [UNESP] (FapUNIFESP (SciELO), 2017)
Meningoencephalitis caused by Bovine herpesvirus 5 (BoHV-5) is an important neurological disease that affects Brazilian cattle herds. The present study investigated the presence of BoHV-5 DNA in cattle diagnosed with meningoencephalitis at Faculdade de Medicina Veterinária e Zootecnia, UNESP - Univ Estadual Paulista from 1980 to 2009. The records obtained from the Large Animal Internal Medicine Service and the Animal Pathology Service were reviewed to identify clinical and epidemiological data from cattle with neurological signs. Excluding rabies cases, we found 115 cases of cattle with neurological signs that had been necropsied. Non-suppurative meningoencephalitis was diagnosed in 28 animals of the 115 initially selected based on histopathological examination of brain tissues. Of these 28 animals, 15 (54%) were positive for BoHV-5 DNA by polymerase chain reaction (PCR) of formalin-fixed paraffin-embedded (FFPE) brain samples. PCR target was 159-bp fragment from the BoHV-5 glycoprotein C gene. The oldest case identified in the present study was from 1988. PCR was a good tool for the diagnosis of BoHV-5 DNA extracted from FFPE tissues, allowing retrospective studies of samples stored for more than 20 years.
Keywords: Cattle diseases; Herpesvirus 5 bovine; Meningoencephalitis; Pathology; Polymerase chain reaction